2022
DOI: 10.1155/2022/8290779
|View full text |Cite|
|
Sign up to set email alerts
|

PTPN11 Gene Mutations and Its Association with the Risk of Congenital Heart Disease

Abstract: Congenital heart disease (CHD) is the most common congenital birth defect, with a prevalence of 8.98‰ of all live births in China. PTPN11 has been known to be closely involved in heart developments. In this research, we carried out whole-exome sequencing in nine CHD families and identified eight rare deleterious missense variants of PTPN11 gene in nine probands by stringently filtering criteria. Sanger sequencing of these probands and their unaffected familiar members revealed that six damaging variants were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The RAS–MAPK signaling pathway is involved in embryonic development during weeks 2 to 8, the critical cardiac development period. Hence, any disturbance to this pathway is likely to cause heart defects [ 21 ]. The SHP-2 protein has an auto-inhibited state in the closed structure by N-SH2–PTP inter-domain interaction.…”
Section: Methodsmentioning
confidence: 99%
“…The RAS–MAPK signaling pathway is involved in embryonic development during weeks 2 to 8, the critical cardiac development period. Hence, any disturbance to this pathway is likely to cause heart defects [ 21 ]. The SHP-2 protein has an auto-inhibited state in the closed structure by N-SH2–PTP inter-domain interaction.…”
Section: Methodsmentioning
confidence: 99%
“…The search for a genetic component in congenital heart disease cases revealed that also more subtle PTPN11 variants may have pathological effects, i.e. on the spatio-temporal control of RAS-mediated signals during embryonic heart development ( Xu et al, 2022 ).…”
Section: Documented Genetic Variabilitymentioning
confidence: 99%
“…Genetic defects responsible for CHD include aneuploidy (presence of an additional chromosome, absence of a chromosome, or deletion/duplication of one arm of a chromosome), copy number variation (deletion or duplication of a segment of a chromosome), and genetic mutations [ 44 , 45 , 46 ]. To date, pathogenic mutations in over 100 genes have been involved in the occurrence of CHD, of which most encode cardiac transcription factors, cell adhesion molecules, signaling pathway proteins, and cardiac structural proteins essential for cardiovascular morphogenesis [ 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. However, CHD is of pronounced genetic heterogeneity, and the genetic determinants causative for CHD in a significant proportion of cases remain to be identified.…”
Section: Introductionmentioning
confidence: 99%